Ablation of polyimide thin-film on carrier glass using 355 nm and 37 ns laser pulses. (February 2020) - Kim, Yoonsuk; Noh, Youngsu; Park, Seungho; Kim, Byung-Kuk; June Kim, Hyoung
Highlights: Ablation of the polyimide (PI) thin-film deposited on glass substrate. A laser beam emitted from 355 nm and 37 ns pulse laser. Backside irradiation on the specimen transferred through the glass substrate. Ablation process based on the bulk photothermal mechanism. Laser-lift off (LLO) process for the fabrication of flexible electronics. Abstract: Ablation of the polyimide (PI) thin-film deposited on glass substrate was investigated theoretically and experimentally to find out the important characteristics during the laser-lift off (LLO) process for the fabrication of flexible electronics. Instead of using conventional ablation induced by the front irradiation on the specimen, the LLO process employs the backside irradiation on the specimen transferred through the glass substrate, assuming that the ablation occurs volumetrically in the narrow region inside the PI film near the PI and glass interface. Experimentally the PI film on glass was exposed to a pulse laser beam emitted from UV laser of 355 nm in wavelength and 37 ns in duration. Depths and morphologies of the ablation spots were observed by the surface profiler and the FE-SEM. Theoretically the ablation process was estimated by the photothermal mechanism, using the one-dimensional heat conduction equation with volumetric absorption of the laser beam. It was shown that the experimental ablation could be described through the theoretical analysis based on the surface and the bulk photothermal models. While the former assumed that the ablation occurred only on the ablation front surface, the latter assumed the ablation was accompanied by the thermal and volumetric bond breakage. In general, the theoretical calculations agreed well with the experimental observations. In particular, the experimental observations of the ablation for the backside irradiation case that was the core phenomenon in the LLO process was explained appropriately by the features predicted using the bulk model.